2022
DOI: 10.1002/jmv.27985
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine breakthrough infection among fully vaccinated healthcare workers in Duhok governorate, Iraqi Kurdistan: A retrospective cohort study

Abstract: The aims of this study were: to determine the incidence of Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) infection among vaccinated healthcare workers (HCWs), assess risk factors associated with the vaccine breakthrough (BT), and compare the effectiveness of vaccine manufacturers against SARS‐CoV‐2 variant of concern among HCWs in Duhok governorate. It is a multicenter retrospective cohort study, which enrolled 944 HCWs through March 2022. COVID‐19 vaccinated HCWs aging 18 and above were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…showed that the 2 viral-vector vaccines JNJ-78436735 (Ad26.COV2.S) and AstraZeneca vaccine (ChAdOx1 nCoV-19) were associated with a higher risk of breakthrough infection compared to BNT162b2 [ 35 ]. This is concordant with a study conducted in Iraq, showing that the AstraZeneca vaccine was more associated with breakthrough infections in comparison with mixed vaccines or BNT162b2 vaccines [ 36 ]. A study in the United Kingdom including a group of vaccinated index patients and unvaccinated ones, compared the probability of infection of people in contact with these 2 groups.…”
Section: Discussionsupporting
confidence: 90%
“…showed that the 2 viral-vector vaccines JNJ-78436735 (Ad26.COV2.S) and AstraZeneca vaccine (ChAdOx1 nCoV-19) were associated with a higher risk of breakthrough infection compared to BNT162b2 [ 35 ]. This is concordant with a study conducted in Iraq, showing that the AstraZeneca vaccine was more associated with breakthrough infections in comparison with mixed vaccines or BNT162b2 vaccines [ 36 ]. A study in the United Kingdom including a group of vaccinated index patients and unvaccinated ones, compared the probability of infection of people in contact with these 2 groups.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have demonstrated the rapid decay of anti-spike antibodies elicited by vaccination ( 6 15 ), as well as those from SARS-CoV-2 infection ( 16 26 ). This is likely a factor in the high frequency of “breakthrough” infections and re-infections among vaccinees ( 27 32 ) and COVID-19-recovered persons ( 33 37 ), although variation of the spike sequence (particularly the receptor binding domain that is the main target of neutralizing antibodies) is a major contributor ( 13 , 29 , 38 42 ). Vaccine protection from severe illness has been more durable ( 43 45 ), which might be due at least in part to cellular immunity and epitope sequences being less affected by spike sequence variation than neutralizing antibodies ( 38 , 46 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of age on the risk of BTI in our study was the opposite of that demonstrated in risk assessment studies conducted in the pre-vaccination era. Additionally, there is some variability in terms of the incidence of BTI in studies conducted during the same period of the pandemic, depending on the prevalent SARS-CoV-2 strain and setting 37 , 38 .
Figure 2 Risk for SARS-CoV-2 breakthrough infection and severe COVID-19 according to age of study participants.
…”
Section: Discussionmentioning
confidence: 99%